Assembling panoramic photos - Bodin, Bertrand (A designer's notebook, 2005)
In this full-color Designer's Notebook, eight expert French photographers reveal their secrets in using Photoshop and a collection of dedicated applications to create extraordinary panoramic photos--including some amazing 360-degree images. For anyone involved with digital imagery or animation, this groundbreaking volume demonstrates a new way of thinking about what's possible and what's required to produce these images. Originally published in France, ""Assembling Panoramic Photos: A Designer's Notebook"" is available in English for the first time. Part art book, part how-to guide, this stunn